Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.15252/emmm.202013502
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cancer intrinsic PI3Kα activity accelerates metastasis and rewires macrophage component

Abstract: Pancreatic ductal adenocarcinoma (PDAC) patients frequently suffer from undetected micro-metastatic disease. This clinical situation would greatly benefit from additional investigation. Therefore, we set out to identify key signalling events that drive metastatic evolution from the pancreas. We searched for a gene signature that discriminate localised PDAC from confirmed metastatic PDAC and devised a preclinical protocol using circulating cell-free DNA (cfDNA) as an early biomarker of micro-metastatic disease … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 87 publications
(84 reference statements)
0
26
0
Order By: Relevance
“…Murine PK4A-Luc (RRID:CVCL_WB21) and R211-Luc 58 cells were cultivated in DMEM GlutaMAX medium (cat. #10566016; Gibco; Thermo Fisher Scientific) supplemented with 10% fetal bovine serum and 1% penicillin/streptomycin (cat.…”
Section: Methodsmentioning
confidence: 99%
“…Murine PK4A-Luc (RRID:CVCL_WB21) and R211-Luc 58 cells were cultivated in DMEM GlutaMAX medium (cat. #10566016; Gibco; Thermo Fisher Scientific) supplemented with 10% fetal bovine serum and 1% penicillin/streptomycin (cat.…”
Section: Methodsmentioning
confidence: 99%
“…The SOLAR-1 phase III study led to the approval of this small molecule that can specifically inhibit p110α by the Food and Drug Administration (FDA) in 2022, recommending its use in PIK3CA-related overgrowth spectrum [ 164 , 165 ]. These promising results have encouraged the hypothesis that alpelisib can successfully treat PC as well, especially taking into consideration that the PI3Kα isoform has a major role in metastatic evolution [ 166 ]. An in vitro study performed on human and murine samples has shown that the inhibition of PI3Kα selectively reduced C36:2 PI-3,4,5-P3 and avoided macrophage accumulation.…”
Section: Pi3k/akt/mtor Inhibitors and Pancreatic Cancermentioning
confidence: 99%
“…An increase in the activation of the PI3K signaling is associated with poor overall survival in PDAC patients [16,17]. Other than the K-Ras-mediated activation of this signaling pathway, the presence of the oncogenic mutation in the PI3KCA gene itself is one of the known mechanisms of its hyperactivation; however, this mutation is found only in a few subsets of PDAC patients [7].…”
Section: Pi3k Signaling Activation In Pdacmentioning
confidence: 99%
“…Tumor intrinsic activation of PI3K signaling, particularly PI3Kalpha, is associated with an inflammatory metastatic phenotype and leads to enhanced accumulation of protumorigenic M2 (CD206+) like macrophages in PDAC [17]. Reprogramming of TAMs towards an anti-tumorigenic M1 phenotype has been associated with increased immunogenicity and increased T cell infiltration within the TME of PDAC.…”
Section: Impact Of Pi3k Inhibition On Tumor-stromal Immune Crosstalk In Pdacmentioning
confidence: 99%